2022
DOI: 10.1111/nejo.12394
|View full text |Cite
|
Sign up to set email alerts
|

Honesty Among Lawyers: Moral Character, Game Framing, and Honest Disclosures in Negotiations

Abstract: Lawyers have broad discretion in deciding how honestly to behave when negotiating. We propose that lawyers’ choices about whether to disclose information to correct misimpressions by opposing counsel are guided by their moral character and their cognitive framing of negotiation. To investigate this possibility, we surveyed 215 lawyers from across the United States, examining the degree to which honest disclosure is associated with lawyers’ moral character and their tendency to frame negotiation in game‐like te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
(81 reference statements)
0
8
0
1
Order By: Relevance
“…The authors concluded that the lawyers violate the rules and practice dishonest behaviors; the antecedent indicated a less ethical and moral mindset, ending with legal consequences. 28…”
Section: Design and Search Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors concluded that the lawyers violate the rules and practice dishonest behaviors; the antecedent indicated a less ethical and moral mindset, ending with legal consequences. 28…”
Section: Design and Search Methodsmentioning
confidence: 99%
“…The authors described attributes of misconduct as bad and unacceptable behaviors by police officers when they use their power (antecedent) to make misguided and illegal decisions, resulting in consequences such as a loss of confidence within the community. 27 On the other side of the world, in the United States of America, Cohen et al 28 investigated lawyers’ honesty in disclosing information, which moral norms should guide. The authors concluded that the lawyers violate the rules and practice dishonest behaviors; the antecedent indicated a less ethical and moral mindset, ending with legal consequences.…”
Section: Design and Search Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…‫يخد(ر‬ ‫امدل‬ ‫لبحدلةا(ن‬ ‫سدن‬ ‫فيدف‬ ‫لب‬ (Hardy, et al, 2015;Wentzel, 2018Wentzel, ,1748Bayar et al, 2020;Peetz & Milyavskaya, 2021 (Hannah et al,2011;Winterich, et al,2013;Cohen et al,2014;Fleeson et al, 2014;;Ding, et al,2018;Patrick, et al,2018;Cohen et al,2021;Zhou et al,2021;Lin & Shek, 2022 ) . ‫د(‬ ‫لبخالقد‬ ‫خ‬ ‫د‬ ‫بقد‬ ‫دلحر‬ ‫لبسد‬ ‫دير ( ) ‫لبسلح(‬ ‫لاجوملج(‬ ‫ل‬ ‫لب‬ ‫لأ‬ ‫رد‬ ‫بل‬ ‫لاجوملج(‬ ‫لبوكلب (ف‬ (Niesta et al,2010;Osswald et al, 2011,392) .…”
unclassified